Collaborative learning and classroom engagement: A pedagogical experience in an EFL Chilean context - Jessica Vega-Abarzua; Javiera Pastene-Fuentes; Constanza Pastene-Fuentes; Camila Ortega-Jiménez; Tamar Castillo-Rodríguez (English Language Teaching Educational Journal, 2022)
In the context of teaching English as a foreign language (EFL), there is growing attention towards collaborative learning and learners’ engagement. Despite the interest on these topics, there is little research in Chile, in the English classroom, about both collaborative learning and learners’ engagement at a school level. Therefore, this study emerged to explore and describe the impact of collaborative-based instruction on learners’ engagement during an intervention of five weeks in a private-subsidized school in the city of Chillan. The participants of the study were 62 female and 70 male students, aged 15 to 17. Based on an action research methodology, the researchers used quantitative and qualitative techniques to collect data which comprised a Likert test (adapted from Alsowat, 2016) administered before and after the intervention, and unstructured observation registered in every lesson by means of field notes learnt from Efrat & Ravid (2020). Our results show that collaborative learning has a direct relationship with learners’ engagement, evidenced in our four classes where behavioral engagement was predominant. Future studies may investigate whether the use of collaborative learning tasks, over a longer period, would still maintain learners’ engagement in the EFL classroom as well as whether behavioral engagement is the most salient dimension among their students.